Handbook of research on digital information technologies innovations, methods, and ethical issues - Hansson, Thomas (Information Science Reference, 2008)
"This book provides a collection of successful designs, defined as communicative relation-building solutions, for individuals and collectives of interlocutors. It includes a longitudinal perspective of past mistakes, current trends and future opportunities, and is a must-have for beginners in the field as well as qualified professionals exploring the full potential of human interactions"--Provided by publisher.